3w-6=6(w-6)

Simple and best practice solution for 3w-6=6(w-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3w-6=6(w-6) equation:


Simplifying
3w + -6 = 6(w + -6)

Reorder the terms:
-6 + 3w = 6(w + -6)

Reorder the terms:
-6 + 3w = 6(-6 + w)
-6 + 3w = (-6 * 6 + w * 6)
-6 + 3w = (-36 + 6w)

Solving
-6 + 3w = -36 + 6w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6w' to each side of the equation.
-6 + 3w + -6w = -36 + 6w + -6w

Combine like terms: 3w + -6w = -3w
-6 + -3w = -36 + 6w + -6w

Combine like terms: 6w + -6w = 0
-6 + -3w = -36 + 0
-6 + -3w = -36

Add '6' to each side of the equation.
-6 + 6 + -3w = -36 + 6

Combine like terms: -6 + 6 = 0
0 + -3w = -36 + 6
-3w = -36 + 6

Combine like terms: -36 + 6 = -30
-3w = -30

Divide each side by '-3'.
w = 10

Simplifying
w = 10

See similar equations:

| 0.04x+0.11(x+300)=59 | | 1n/0.99n | | 9(x+1)=-3x+21 | | t=2π√l/g | | (7x+59)=(8x+46) | | (2.5-x)/(2.5-1)=0.66 | | 10x-26+16=8x | | (x+15)2=81 | | ((4x-5)/5)-8=-11 | | 5y-10-64=0 | | y-5=-4(x+4) | | 6x^2=-30 | | 11=3(v-7)-8v | | 2x^3-13x^2-12=0 | | 3x+4(x+2)=5(x+2) | | (2.5jt-z)/(2.5jt-1jt)=0.66 | | (70-z)/(70-50)=0.3 | | (70-z)/(70-20)=0.3 | | (7-z)/(7-2)=0.25 | | (7000-z)/(7000-2000)=0.25 | | -7+7d=8 | | 3x+6xy=4y+2 | | 2t^2-9t+16=15-4t^2 | | 6x-12=4(x-2) | | (z-7000)/5000=0.25 | | 19x+rw=-37x+w | | 7x=49x | | 6x^2-47+15=0 | | 2nr=c | | a+x=2 | | t=3+3n | | 4m=3n+8 |

Equations solver categories